Lived experience perspectives guiding improvements to the Systematic Tailored Assessment for Responding to Suicidality protocol - Hawgood, Jacinta; Betterridge, Carmen; Kõlves, Kairi; Edwards, Bronwen; Spence, Susan H.; Arensman, Ella; De Leo, Diego; Ownsworth, Tamara (Frontiers in Psychiatry, 2023)
Background and aims Suicide risk assessment protocols have traditionally been developed by clinical or research experts in suicidology, with little formal involvement of those with a lived experience of suicide. This study broadly aimed to seek lived experience perspectives of the Systematic Tailored Assessment for Responding to Suicidality (STARS) protocol A further aim was to elicit lived experience suggestions for wording and language used in the existing items within sections of the STARS protocol (STARS-p). Method Participants were 33 adults (Female = 64%) with a lived experience of suicide, who attended a virtual research workshop at the National Lived Experience of Suicide Summit (2021). After being educated about STARS-p, participants provided their overall perceptions of STARS-p as well as suggestions for rewording and language use across the sections of STARS-p. Their responses were gathered using a virtual online platform for live electronic data collection. A three-phase process of qualitative content analysis was used, engaging both inductive and deductive approaches to explore study aims one and two, respectively. The Consolidated Criteria for Reporting Qualitative Research was followed to enhance quality of reporting. Results Qualitative content analysis of participants’ views of the STARS-p reflected three main categories, namely, STARS philosophy; What STARS aspires to; and Continuity of care and meeting needs. Responses characterized participants’ perceptions of the core purpose of STARS-p and ways for refining or adapting it to suit diverse needs and settings. Based on deductive content analysis, suggested modifications to wording of items and additional items to extend sections were identified. Conclusion The study yielded novel perspectives from those with a lived experience of suicide, which will inform improvements to the next edition of STARS-p. The STARS training (required for licensed use of the protocol) will be updated accordingly, in line with these results.